Examining the contributions of desirable difficulty and reminding to the spacing effect. - Maddox, Geoffrey B.; Pyc, Mary A.; Kauffman, Zachary S.; Gatewood, Jessica D.; Schonhoff, Aubrey M. (Memory & Cognition, 2018)
Although substantial evidence indicates that spacing repeated study events with intervening material generally enhances memory performance relative to massing study events, the mechanism underlying this benefit is less clear. Two experiments examined the role of reminding difficulty during the acquisition of material in modulating final memory performance for spaced repetitions utilizing recognition (Experiment 1) and recall tests (Experiment 2). Specifically, participants studied a list of words presented one or two times separated by one or five items. On each trial participants reported whether the item had been previously presented (i.e., repetition detection judgment), and the response latency served as a proxy for reminding difficulty such that longer response latencies reflected more difficult reminding. A third experiment extended this paradigm with the inclusion of a massed condition and novel lag conditions (three and ten items). Results revealed significant lag effects in final test performance across experiments despite comparable repetition detection difficulty between lag conditions during acquisition. Moreover, results from within-participant point-biserial analyses and mediation analyses converged on overall performance measures in suggesting that repetition detection difficulty failed to modulate final test performance in the current paradigm. Discussion considers the implications of the current results for mechanisms proposed to underlie the benefits of spaced study and spaced retrieval practice.